Study of Promoter Methylation Patterns of HOXA2, HOXA5, and HOXA6 and Its Clinicopathological Characteristics in Colorectal Cancer - Li, Daojiang; Bai, Yang; Feng, Zhicai; Li, Wanwan; Yang, Chunxing; Guo, Yihang; Lin, Changwei; Zhang, Yi; He, Quanyong; Hu, Gui; Li, Xiaorong (Frontiers in Oncology, 2019)
Research on DNA methylation offers great potential for the identification of biomarkers that can be applied for assessing an individual’s risk for cancer. In this article, we try to find the ideal epigenetic genes involved in colorectal cancer (CRC) based on database and our cohort. The top 20 genes with an extremely high frequency of hypermethylation in CRC were identified in database. Remarkably, 3 HOXA genes were included in this list and ranked at the top. The percentage of methylation in the HOXA5, HOXA2 and HOXA6 genes in CRC were up to 67.62%, 58.36% and 31.32%, respectively. Paired colorectal tumor samples and adjacent non-tumor colorectal tissue samples and 4 CRC cell lines were selected for MethylTarget TM assays. The results demonstrated that CRC tissues and cells had a stronger methylation status compared with adjacent non-tumor colonic tissue samples. The ROC curves for HOXA genes show excellent diagnostic ability in distinguishing tissue from healthy individuals and CRC patients, especially for Stage I patients. An association analysis between the methylation pattern of HOXA genes and clinical indicators was performed and found that HOXA2 methylation was significantly associated with age, N, stage, M, lymphovascular invasion, perineural invasion, lymph node number. HOXA5 methylation was associated with age, T, M, stage and tumor status, and HOXA6 methylation was associated with age and KRAS mutation. Notably, we found that the highest methylation of HOXA5 and HOXA2 occurs in the early stages of colorectal cancer tissues such as stage I, N0, MO and non-invasive tissues. The methylation levels declined as tumors progressed. However, methylation level at any stage of the tumor was still significantly higher than in normal tissues (p<0.0001). The mRNA of the 3 HOXA genes was downregulated in early tumor stages due to hypermethylation of CpG islands adjacent to the promoters of the genes through bisulfite sequencing assay. In addition, hypermethylation of HOXA5 and HOXA6 mainly occurred in patients <60 years old and with MSI-L, MSS, CIMP.L and non-CIMP tumors. Together, this suggests that epigenetic silencing of 3 adjacent HOXA genes may be an important event in the progression of colorectal cancer.